CLINICAL AND MORPHOLOGICAL EVALUATION OF THE EFFECTIVENESS OF USING RADIO WAVE AND HIGH-FREQUENCY ELECTROSURGERY TECHNOLOGIES FOR THE TREATMENT OF COMBINED ANORECTAL DISEASES - Balytskyy, V.V.; Zakharash, M.P.; Kuryk, O.G. (World of Medicine and Biology, 2022)
Nowadays, the number of proctological diseases is significantly increasing, among which the share of combined anorectal pathology reaches from 35 to 65 %. The results of surgical treatment of 635 patients with combined anorectal diseases who were divided into 4 research groups have been shown. After operations, 30 patients in each group underwent morphological investigations of the anal canal and rectal tissues to study the depth of coagulation necrosis. In the case of using the high-frequency electrosurgical device with a frequency of 330 kHz was formed layer of coagulation necrosis with a thickness of 0.302±0.107 mm, in the case of using a high-frequency electrosurgical device with frequency 375 KHz – 0.208±0.097 mm, in case of using a high-frequency electrosurgical device with frequency 450 KHz – 0.194±0.090 mm and in case of using the radio-wave device with frequency 3.8–4.0 MHz – 0.189±0.085 mm. Using these technologies reduces the operation duration, volume of bleeding, and intensity of the postoperative pain and prevents the formation of anal strictures.
Keywords: radio-wave surgery device; high-frequency electrosurgery devices; combined anorectal diseases